2014
DOI: 10.4315/0362-028x.jfp-14-200
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Salmonella and Campylobacter on Broiler Chickens from Farm to Slaughter and Efficiency of Methods To Remove Visible Fecal Contamination

Abstract: A study was conducted to investigate the prevalence of Salmonella and Campylobacter from farm to slaughter. The efficiency of trimming and water spray (490 to 588 kPa pressure) on the removal of visible fecal contamination from broiler carcasses before chilling was also investigated. Drag swabs were used to sample litter from the farm houses. Samples of ceca and carcasses without and with visible fecal contamination before and after trimming or spray washing of fecal contamination were taken during slaughter o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 31 publications
(36 reference statements)
5
25
1
2
Order By: Relevance
“…Entretanto, pesquisas que utilizaram suabes de arrasto para isolar Salmonella spp. em outras granjas obtiveram resultados positivos, com a prevalência variando entre 1,95% e 11,4% (Boni et al 2011, Giombelli & Gloria 2014, Voss-Rech et al 2015, Pandini et al 2015. O método de coleta com auxílio de suabes de cloaca pode ter influenciado na baixa positividade observada nas amostras de frangos vivos desse estudo e naqueles com resultados semelhantes.…”
Section: Resultados E Discussão Prevalência De Salmonella Spp Em Fraunclassified
See 1 more Smart Citation
“…Entretanto, pesquisas que utilizaram suabes de arrasto para isolar Salmonella spp. em outras granjas obtiveram resultados positivos, com a prevalência variando entre 1,95% e 11,4% (Boni et al 2011, Giombelli & Gloria 2014, Voss-Rech et al 2015, Pandini et al 2015. O método de coleta com auxílio de suabes de cloaca pode ter influenciado na baixa positividade observada nas amostras de frangos vivos desse estudo e naqueles com resultados semelhantes.…”
Section: Resultados E Discussão Prevalência De Salmonella Spp Em Fraunclassified
“…A ocorrência de Salmonella spp. também é descrita na granja, com variações entre 1,95% e 11,4% (Boni et al 2011, Ravagnani et al 2012, Giombelli & Gloria 2014, Voss-Rech et al 2015, Pandini et al 2015. Em relação aos frangos vivos, a frequência relatada é muito baixa, cerca de 0,2% (Ravagnani et al 2012, Mezalira et al 2014, Bezerra et al 2016.…”
Section: Introductionunclassified
“…This result is similar to the prevalence reported in Venezuela (23%; n = 332) [ 32 ]. In contrast prevalence in Brazil was only of 5% (n = 40) [ 33 ] and in Colombia 65% (n = 315) [ 34 ]. On the other hand, for the European Union member states and 3 European non-member states an overall Salmonella prevalence of 3.37% at farm level was reported with rates varying from 0.08% in Norway to 13.48% in Hungary in 2014 [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the high detection rate of SE in chicken feces and cloacal swab isolates, some isolates were found to be in serogroups B and C1, whereas only 2 isolates (crow and chick intestine) were NS with the available antisera (Table). In previous studies, which used similar avian sample types such as cloacal swabs, feces, and intestine, detection of SE was previously indicated by Kinde et al (28), while a higher prevalence of other serogroups such as B (29) and C1 (26) was also reported. As another serotyping finding in our study, all chicken drag swab isolates were SE, which, although contrasted to the relatively lower SE incidences of Kinde et al (28) and Kahya et al (11), is in agreement with other previous reports that suggested the drag swab as an effective sample type in SE detection from environmental samples of layer flocks (28,29).…”
Section: Discussionmentioning
confidence: 69%